Impacts of the Physico-chemical Properties of Al-Chibayish Water Marshes on The Biodiversity of Phytoplankton - Jaafar, Firas AbdulHassan; Abdulwahhab, Ahmed Saad (Iraqi Journal of Science, 2021)
Phytoplankton, as one of the most important primary producers in aquatic ecosystems, has been widely used to indicate the health of ecosystems. Nine physico-chemical parameters of water, as well as the phytoplankton community, of Al-Chibayish marsh were studied. Samples were collected from four sites and analyzed every two months from January to October 2019. Seasonal variations in physical and chemical properties were observed at all sites during the study period. The results indicated that 154 species of phytoplankton were recorded. The highest percentage of species was recorded to be 64.28% for Bacillariophyceae (diatoms) (Centrales 3.24% and Pennales 61.03%), followed by Chlorophyceae (16.23%), Cyanophyceae (11.68%), and Charophyceae and Euglenophyceae (3.24%), while Pyrrophyceae recorded the lowest value (1.29%) The numbers of phytoplankton species were 102, 94, 102, 99 in sites 1, 2, 3 and 4 ,respectively, during the study period. The total density of phytoplankton ranged from 223.769 cells x103 during January to 2784.693 cells x103 during September in site 2, with a clear increase during March and September, while the lowest number was 223.796 - 237.248 cells x103 in January and May, respectively. The dominance of diatoms was observed in all sites by 49.07% of the total density of phytoplankton, while the lowest abundance was 0.04% for the Pyrrophyceae. The results of the statistical analysis showed significant differences among sites and months, concerning the physical, chemical, and biological factors measured during the study period, at p-value <0.05.